Policiamento ostensivo em áreas de risco: entre o prescrito e o real - Resangela Pinheiro de Sousa (2013)
The study was conducted with two teams of the Military Police of Minas Gerais (PMMG), the Expert Group on Risk Areas (GEPAR), which act in policing in slums and villages located in neighborhoods in the metropolitan region of Belo Horizonte. In peculiarity of service prevention, repression and qualified social protection - under the standards of service - operate with the police order to ensure the safety of residents, preventing gangs involved in drug trafficking determine the rules in place. This thesis aimed to understand the work activity of these officers, in situations of patrolling in hazardous areas. This is a qualitative research guided by the principles of participant observation in incursions with the military police in the territory where they operate. These incursions in everyday work situations were prepared and analyzed according to the theoretical-methodological of Ergonomics and from Ergology what this deepens and incorporates the contributions of the first - provided important tools to reconstruct the view of police activity on the work done and allowed to take another look at the public security policies as the value of the common good. The results obtained in empirical terms, pointed to the difficulties faced by the police activity in the face of institutional and local standards, to aim to balance the tripod of prevention, repression and social protection in places of social conflictualities. This is because work always entails judgments and arbitrations in debate with the standards in the face of "infidelity of the middle." The study indicated that as the police into activity within the formalized knowledge, seized in vocational training, are repositioned according to the local norms and values.It was observed that the challenge is to form PMMG police for risky activities, in the context in which skills are numerous and indispensable to guide your power to act in the situation. Thus, it is possible to understand the richness present in the real work, it is necessary to recreate and adapt your own activity, through the dialectic of uses by itself for itself and use of itself for others.